2014
DOI: 10.1134/s0006297914010076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potential-dependent potassium uptake on production of reactive oxygen species in rat brain mitochondria

Abstract: The effect of potential-dependent potassium uptake on reactive oxygen species (ROS) generation in mitochondria of rat brain was studied. It was found that the effect of K+ uptake on ROS production in the brain mitochondria under steady-state conditions (state 4) was determined by potassium-dependent changes in the membrane potential of the mitochondria (ΔΨm). At K+ concentrations within the range of 0-120 mM, an increase in the initial rate of K(+)-uptake into the matrix resulted in a decrease in the steady-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
5
11
0
Order By: Relevance
“…Using indirect methods (polarography and light absorbance to monitor the oxygen consumption and mitochondrial volume changes), we have shown full activation of native liver mK ATP channel elicited by ≤500 nM of DZ [55]. Likewise, with the same methods we observed that channel blockage by glibenclamide and 5-HD did not require the presence of Mg·ATP in isolated liver and brain mitochondria [55,56].…”
Section: Mkatp Channels As the Target Of Diazoxidementioning
confidence: 59%
See 3 more Smart Citations
“…Using indirect methods (polarography and light absorbance to monitor the oxygen consumption and mitochondrial volume changes), we have shown full activation of native liver mK ATP channel elicited by ≤500 nM of DZ [55]. Likewise, with the same methods we observed that channel blockage by glibenclamide and 5-HD did not require the presence of Mg·ATP in isolated liver and brain mitochondria [55,56].…”
Section: Mkatp Channels As the Target Of Diazoxidementioning
confidence: 59%
“…Thus we obtained a reliable appraisal of the share of mK ATP channel in potassium transport and mitochondrial uncoupling by DZ in liver mitochondria [55]. Using DZ as pharmacological tool, we also established the share of mK ATP channel in membrane depolarization and suppression of potential-dependent ROS production in brain mitochondria, which was confirmed independently by using K ATP channel blockers, glibenclamide and 5-HD [56].…”
Section: Appraisal Of Functional Consequences Of K Atp Channels Openimentioning
confidence: 61%
See 2 more Smart Citations
“…Peripheral electrical stimulus is one common method used in neurophysiology study, in which caudal sensory nerve action potentials [92] (caudal SNAPs) are recorded centrally from the tail. As the high oxidative metabolism in the brain, the function of brain mitochondria, which is easily isolated by differential centrifugation, is a good index to evaluate brain nerve injury [93,94]. The respiratory chain [95] of the mitochondria provides opportunities for potential mechanism study.…”
Section: Nervous Systemmentioning
confidence: 99%